Variations in the spatial distribution of areas of economic growth and stagnation in Poland: Determinants and consequences - Churski, Paweł (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2014)
This study seeks to identify the spatial distribution of and changes in areas of economic growth and stagnation in Poland resulting from spatial differences in the process of the country’s socio-economic advancement. The research covered two spatial systems, NUTS 2 and NUTS 4, and embraced the following steps: (1) identification of the spatial distribution of areas of economic growth and stagnation, by region and subregion, and of its determinants; (2) analysis of variations in the spatial distribution of areas of economic growth and stagnation, by region and subregion, and of its consequences; and (3) conclusions from the development trajectories identified and recommendations for intervention measures to be taken under cohesion policy. The results presented here come from one of the stages of a research conducted under the project Socio-economic development and the formation of areas of economic growth and stagnation, funded by the National Science Centre (N N306 791940). The project is implemented by a team of staff members of the Department of Regional Analysis of the Institute of Socio-Economic Geography and Spatial Management, Adam Mickiewicz University in Poznań, headed by the present author.
Keywords: differences; growth; stagnation; areas; region; subregion; Poland